Dynamic covalent chemistry with azines. Issue 79 (14th September 2022) - Dascalu, Anca-Elena; Halgreen, Lau; Torres-Huerta, Aaron; Valkenier, Hennie
Abstract : Azines provide an attractive balance in dynamic covalent chemistry, with rapid exchange in acidic conditions and good stability in the presence of water. Abstract : Dynamic covalent chemistry is used in many applications that require both the stability of covalent bonds and the possibility to exchange building blocks. Here we present azines as a dynamic covalent functional group that combines the best characteristics of imines and acylhydrazones. We show that azines are stable in the presence of water and that dynamic combinatorial libraries of azines and aldehydes equilibrate in less than an hour.